A Demonstration Project for the Utility of Kinect-Based Educational Games to Benefit Motor Skills of Children with ASD. Issue 6 (December 2019) - Vukićević, Sanja; Đorđević, Mirjana; Glumbić, Nenad; Bogdanović, Zorica; Đurić Jovičić, Milica
Motor disorders often accompany autism spectrum disorder (ASD), although they are not included in its diagnostic criteria. Slower motor development is evident in early childhood in this population, making early motor skills intervention advisable. As educational games and modern technology can represent new forms of treatment, this study evaluated four Kinect-based visuo-motor games called Fruits that were specially designed for this research. We sought to test whether children with ASD would show behavior changes during their game play and whether any effects would generalize to another game called Rackets. The study included 10 elementary school children with ASD, aged 9-13 years, who were divided into (a) an experimental group ( n = 5) who, in addition to standard treatment, played Fruits once a week for a 5-week period and Rackets both before and after the 5-week period and (b) a control group ( n = 5) who received only standard treatment during this period and also played Rackets before and after it. We found significant improvements in gross motor skills and successful generalization of acquired skills among children in the experimental group relative to the control group. The experimental group also showed an increase in positive emotions and a decrease in loss of attention while playing the games. These preliminary findings indicate a motor skill benefit for children with ASD who play Kinect-based educational games, but further research is needed to replicate and expand these findings with larger participant samples.